RTDS implementation of an improved sliding mode based inverter controller for PV system. (May 2016) - Islam, Gazi; Muyeen, S.M.; Al-Durra, Ahmed; Hasanien, Hany M.
Abstract: This paper proposes a novel approach for testing dynamics and control aspects of a large scale photovoltaic (PV) system in real time along with resolving design hindrances of controller parameters using Real Time Digital Simulator (RTDS). In general, the harmonic profile of a fast controller has wide distribution due to the large bandwidth of the controller. The major contribution of this paper is that the proposed control strategy gives an improved voltage harmonic profile and distribute it more around the switching frequency along with fast transient response; filter design, thus, becomes easier. The implementation of a control strategy with high bandwidth in small time steps of Real Time Digital Simulator (RTDS) is not straight forward. This paper shows a good methodology for the practitioners to implement such control scheme in RTDS. As a part of the industrial process, the controller parameters are optimized using particle swarm optimization (PSO) technique to improve the low voltage ride through (LVRT) performance under network disturbance. The response surface methodology (RSM) is well adapted to build analytical models for recovery time ( Rt ), maximum percentage overshoot (MPOS), settling time ( Ts ), and steady state error ( Ess ) of the voltage profile immediate after inverter under disturbance. A systematic approach of controller parameter optimization is detailed. The transient performance of the PSO based optimization method applied to the proposed sliding mode controlled PV inverter is compared with the results from genetic algorithm (GA) based optimization technique. The reported real time implementation challenges and controller optimization procedure are applicable to other control applications in the field of renewable and distributed generation systems. Graphical abstract: Highlights: A novel approach of testing dynamics and control aspects of PV system is presented. Real time implementation of a sliding mode based inverter controller is detailed. A systematic approach to determine controller parameter is demonstrated. Particle swarm optimization technique is used in determining controller parameters. Proposed control and optimization techniques can be applied to any grid-tied inverter.